2015
DOI: 10.1186/s12889-015-1899-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of students' willingness to accept a measles–mumps–rubella booster vaccination during a mumps outbreak: a cross-sectional study

Abstract: BackgroundDespite high vaccination coverage, a mumps outbreak that affected mainly vaccinated university students and their contacts took place in the Netherlands in the period 2009–2012. We presented university students with a hypothetical case in which we offered them a measles, mumps, and rubella (MMR) booster vaccination to control the mumps outbreak. The aim of this study was to get insight into the determinants of university students' willingness to accept this vaccination.MethodsA questionnaire containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…As demonstrated by their scores on the benefits of vaccination questions, respondents, with and without waivers, ranked vaccinations as an effective way to control and prevent the onset of disease as the highest ranked benefits. This finding aligns with another study among university students that found the number one priority of vaccination to be protection against diseases that are life threatening or that greatly impact the quality of life ( 38 ). This finding is important because it provides the university healthcare community with insight into the viewpoint of the reasons why a young adult population views vaccinations as beneficial.…”
Section: Discussionsupporting
confidence: 90%
“…As demonstrated by their scores on the benefits of vaccination questions, respondents, with and without waivers, ranked vaccinations as an effective way to control and prevent the onset of disease as the highest ranked benefits. This finding aligns with another study among university students that found the number one priority of vaccination to be protection against diseases that are life threatening or that greatly impact the quality of life ( 38 ). This finding is important because it provides the university healthcare community with insight into the viewpoint of the reasons why a young adult population views vaccinations as beneficial.…”
Section: Discussionsupporting
confidence: 90%
“…Other papers have focused instead on demand side factors, examining the determinants of vaccine hesitancy and the role of individual factors influencing uptake. Donkers et al ( 2015 ) show how the perceived seriousness of Mumps increases vaccination rates among Dutch university students. Similarly, in the context of the current pandemic, Viswanath et al ( 2021 ) show how individual perception of risk of becoming infected or by proximity with casualties from the disease, decreases vaccine hesitancy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%